Research on the Integration of Media Literacy Innovative Concept and Entrepreneurship Education and Digital Dynamic Creative Expression Talents - Zhang, Jie; Zhang, Mingming; Liu, Yaqian; Lyu, Ruimin; Cui, Rongrong (Frontiers in Psychology, 2021)
The rapid development of digital technology has brought a variety of forms of digital media. In these emerging media, with the support of high-performance computers, more and more dynamic performance has become possible, and the public has been cultivated a preference for dynamic content cognition. In this study, based on the basic characteristics of visual perception to the cognition of motion form, aims to cultivate the cognitive literacy of Pan digital media with innovative concept and entrepreneurship education, and explore the cognition and innovative expression methods of dynamic language in digital design. The research leads the static oriented morphological exploration and expression to the dynamic expression and thinking of the same concept object. Set up the basic thinking steps for students from "static" to "dynamic", and encourage them to use "Synaesthesia", "metaphor" and other ways to carry out "dynamic expression" level of emotional association. In the experiment, two different ways of design expression, static and dynamic, are required to design and evolve graphics. In this study, 50 freshmen were selected as the training objects for the planning and training of design thinking and performance means. In the visual elaboration and expression of the inner emotion of the same content with innovative concept and entrepreneurship education not only the changes and combinations of the graphics themselves should be innovated, but also the emotional characteristics of the more abstract graphics expressed in the movement should be more perceived and innovative idea. Finally, the feedback data of students' thinking and cognition differences in the two stages of expression were obtained through the questionnaire, and analyzed and compared. The experimental results show that after the training, students' ability with innovative concept and entrepreneurship education in dynamic expression means, consciousness and perception has been significantly improved. At the same time, it also provides a new vision and specific implementation method for the future training of digital dynamic innovation expression ability and the cultivation of digital media literacy innovative concept and entrepreneurship education.